Toward a participatory VGI methodology: crowdsourcing information on regional food assets. Issue 11 (2nd November 2018) - Fast, Victoria; Rinner, Claus
ABSTRACT: Local knowledge has been underrepresented in food-related policies and planning. The goal of this research was to engage members of a local food community and generate volunteered geographic information (VGI) on community food assets. During active data collection, over 200 food assets were reported. This paper details the systematic approach used to create VGI, which emphasizes the socio-cultural context surrounding the mapping technology. The project began with an identified need to connect to and learn from the local food community. The participants were drawn from active food system stakeholders, and a Geoweb infrastructure was selected based on publicly available crowdsourcing tools. The resulting VGI is presented according to system functions: input (Web traffic, contributors, input types), management (contribution vetting, privacy), analysis (typology of input), and presentation (sharing the submitted data). Despite limitations, this study revealed a hyper-local and community-driven perspective on food assets, opened access to government and private data, and increased the transparency and accessibility of information on the regional food system. This research also revealed that there is a growing need for intermediaries who can bridge the gap between experts in the subject matter and experts in digitally enabled participation, and a need for non-government open data repositories.